SUMOylation of PDGF receptor α affects signaling via PLCγ and STAT3, and cell proliferation - Kehuan Wang; Natalia Papadopoulos; Anahita Hamidi; Johan Lennartsson; Carl-Henrik Heldin (BMC Molecular and Cell Biology, 2023)
Abstract Background The platelet-derived growth factor (PDGF) family of ligands exerts their cellular effects by binding to α- and β-tyrosine kinase receptors (PDGFRα and PDGFRβ, respectively). SUMOylation is an important posttranslational modification (PTM) which regulates protein stability, localization, activation and protein interactions. A mass spectrometry screen has demonstrated SUMOylation of PDGFRα. However, the functional role of SUMOylation of PDGFRα has remained unknown. Results In the present study, we validated that PDGFRα is SUMOylated on lysine residue 917 as was previously reported using a mass spectrometry approach. Mutation of lysine residue 917 to arginine (K917R) in PDGFRα substantially decreased SUMOylation, indicating that this amino acid residue is a major SUMOylation site. Whereas no difference in the stability of wild-type and mutant receptor was observed, the K917R mutant PDGFRα was less ubiquitinated than wild-type PDGFRα. The internalization and trafficking of the receptor to early and late endosomes were not affected by the mutation, neither was the localization of the PDGFRα to Golgi. However, the K917R mutant PDGFRα showed delayed activation of PLC-γ and enhanced activation of STAT3. Functional assays showed that the mutation of K917 of PDGFRα decreased cell proliferation in response to PDGF-BB stimulation. Conclusions SUMOylation of PDGFRα decreases ubiquitination of the receptor and affects ligand-induced signaling and cell proliferation.